Technology Leadership Barriers for Women Engineers in Latin AmericanStartups - Martinez Almendares, Wendy Stephanie; Aguilar Montoya, Douglas Adalberto (LACCEI, 2025)
The inequality dynamics in the Latin American technological entrepreneurial ecosystem demonstrate the persistence of systemic barriers that limit female access to leadership positions in technology-based startups. This study examines the implicit exclusion mechanisms that shape the "digital glass ceiling" through a mixed analysis involving 847 female engineers across 12 countries in the region, with special emphasis on El Salvador where it was documented that only 8.3% of technology startups have women as principal co-founders. Through digital ethnographic methodology, professional social network analysis, and in-depth interviews with 156 ecosystem protagonists, four critical dimensions were identified: algorithmic micromachisms in funding platforms (evidenced by the 3% of venture capital allocated to female founders), unconscious biases in executive selection processes, precariousness in business mentorship networks, and asymmetries in the valuation of technical versus relational competencies. In the Salvadoran context, where 64% of microenterprises are led by women but only 12% access technological financing, the findings reveal that barriers transcend quantitative aspects to constitute a phenomenon of cultural invisibilization of female leadership in high-innovation sectors. An inclusive entrepreneurial ecosystem framework is proposed that integrates affirmative financing policies, debiasing protocols in venture capital, and culturally situated technological mentorship platforms for the region.